2019
DOI: 10.3390/genes10110921
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-11 Expression Promotes Invasiveness and Correlates with Survival in Human Pancreatic Ductal Adeno Carcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer, proving difficult to manage clinically. Wnt-11, a developmentally regulated gene producing a secreted protein, has been associated with various carcinomas but has not previously been studied in PDAC. The present study aimed to elucidate these aspects first in vitro and then in a clinical setting in vivo. Molecular analyses of Wnt-11 expression as well as other biomarkers involved qRT-PCR, RNA-seq and siRNA. Proliferation was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
(79 reference statements)
2
11
0
Order By: Relevance
“…This correlates with the differences observed in protein levels of the PAD isozymes in the cell lines and lack of positive signal for PAD4 at expected molecular size, also pointing to a negligible role for PAD4 in PDAC, while PAD2 was the most prominent isozyme. Some differences were furthermore observed between the two PDAC cell lines under study, pointing to stronger effects of PAD inhibitors in Panc-1 cells, which, interestingly, also showed substantial response to PAD3 inhibitor, which may correlate with previous observations that this cell line contains neuronal-like/stem-like properties [104].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This correlates with the differences observed in protein levels of the PAD isozymes in the cell lines and lack of positive signal for PAD4 at expected molecular size, also pointing to a negligible role for PAD4 in PDAC, while PAD2 was the most prominent isozyme. Some differences were furthermore observed between the two PDAC cell lines under study, pointing to stronger effects of PAD inhibitors in Panc-1 cells, which, interestingly, also showed substantial response to PAD3 inhibitor, which may correlate with previous observations that this cell line contains neuronal-like/stem-like properties [104].…”
Section: Discussionsupporting
confidence: 78%
“…PAD3 has been associated with neuronal stem cell properties [ 92 ] and found, for example, to be elevated in specific GBM cell lines, which may therefore also have stronger stem-like properties as GBM are known for stem-ness [ 15 , 17 ]. Importantly, previous PDAC in vitro studies reported that Panc-1 cells display most neuronal/stem-like properties [ 104 ], which may cause it to reflect a more aggressive form and also highlight possible roles for PAD3 in such stem-like cancers. Therefore it will be of great interest to further investigate a link between PAD3 and cancer stem-ness in a wider range of cancers and cancer cell lines, including PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by real-time qPCR was performed using Taq SYBR Green premix (Qiagen, Manchester, United Kingdom), as reported before. Relative levels of mRNA expression were calculated using the Comparative CT/2-ΔΔCT method [ 33 , 34 ]. RPII (RNA polymerase II) was used as the reference gene.…”
Section: Methodsmentioning
confidence: 99%
“…The cDNA was generated by the reverse transcriptase reaction and used for real-time PCR (qRT-PCR). The following genes were studied: NSE, Asl1, Hes6, Nanog, Twist, Snail, E-cadherin, and Wnt-11 (corresponding primer sequences given previously [32,33]). Analysis by real-time qPCR was performed using Taq SYBR Green premix (Qiagen, Manchester, United Kingdom), as reported before.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Wnt-11 is a member of the Wnt signaling pathway, which is activated during embryogenesis for normal development, and recently, its upregulation was found in various malignancies, including PCa [12][13][14]. Wnt-11 is found to be upregulated in metastatic disease, and more importantly, it has been shown that it involves in TGF-β signaling pathways during the epithelial-to-mesenchymal transition (EMT), which is important for prostate cancer cell migration and invasion [13].…”
Section: Introductionmentioning
confidence: 99%